Diplomatic Collaborative Solutions to Assure the Adoption of the European Single Market Amid the COVID-19 Pandemic - Logar, Silvia; Alessandro, Rizzardo (Frontiers in Public Health, 2021)
As the COVID-19 crisis has shown, the lack of harmonized and coordinated actions superseding national borders represented a limit to the full implementation of already existing legally binding instruments at the European level. Recognizing that the existing levels of globalization have contributed to accelerate the large-scale transmission of viruses and increased the likelihood of a pandemic public health crises, the aim of this paper is to highlight the importance of greater bilateral cooperation to mitigate the health and economic impact from the COVID pandemic. The article focuses on the implementation of diplomatic collaborative systems to assure the full implementation of the European Single Market as well as the adoption of standardized health information platforms as part of pandemic preparedness and control measures.